ABDURRAHMAN AZ-ZAHIRI'S RELIGIOUS AND POLITICAL THOUGHT CONTROVERSY (International Conference on Social and Islamic Studies, 2022)
This paper examines an Islamic figure from Yemen who later became very popular in the story of the Aceh war (1873-1912). In many studies of the history of the Archipelago he has become a controversial figure, on the one hand he is considered to be part of the heroes of the Kingdom of Aceh for being a fighter in many wars against the colonialists but on the other hand he is considered a traitor because in his diplomatic story with the colonialists he presented detrimental agreements the kingdom of Aceh and benefit themselves. So this paper will examine how the actual socio-historical context of Abdurrahman Az-Zahir's life journey, especially how the context of the cities of Yemen gave birth to Islamic figures who eventually mushroomed into the archipelago from the past to the present, and how also the form of Abdurrahman Az-Zahir's thoughts in his context as a scholar, political figure and diplomat of the kingdom of Aceh. And as for the results of the literature search that has been carried out, it is concluded that the Aceh sultanate experienced ups and downs of glory around the 19th century. Especially after Dutch power came with troop strength and politics of playing one against the other which was carried out to divide the internal strength of the Aceh kingdom. In this process, Abdurrahman Az-Zahir became part of the kingdom, which later greatly determined the shape and direction of his thoughts, both in the religious and political contexts. As for the role given by Abdurrahman az-Zahir for the kingdom in his position as a scholar, royal official and troop leader against the Dutch. Particularly and clever diplomacy with foreign parties to offer cooperation and peace. But it's a shame that in his story, there is a story of betrayal after negotiating and choosing a strategy at the end of his struggle. He was accused of being a traitor because he stopped fighting and received gifts from the Dutch. In fact, all of this cannot be separated from the politics of pitting the Dutch against each other in destroying the power of the Aceh kingdom.